Used television strategies to seduce target audience of chile’s newscast - Antezana Barrios, Lorena (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
Nowadays, the evening television newscast occupies a privileged space as a daily social ritual in which television viewers set aside time to “inform themselves” about the events that provide them with what they need to function in society. These events are arranged and structured using a fundamentally narrative logic, which is employed in a unique way by each television channel. This method of arranging the stories is a strategy used by the television channel to seduce and retain its target audience.